Update on perioperative hypersensitivity reactions: joint document from the Brazilian Society of Anesthesiology (SBA) and Brazilian Association of Allergy and Immunology (ASBAI) - Part II: etiology and diagnosis - Solé,Dirceu (2020)
Abstract This second joint document, written by experts from the Brazilian Association of Allergy and Immunology (ASBAI) and Brazilian Society of Anesthesiology (SBA) concerned with perioperative anaphylaxis, aims to review the pathophysiological reaction mechanisms, triggering agents (in adults and children), and the approach for diagnosis during and after an episode of anaphylaxis. As anaphylaxis assessment is extensive, the identification of medications, antiseptics and other substances used at each setting, the comprehensive data documentation, and the use of standardized nomenclature are key points for obtaining more consistent epidemiological information on perioperative anaphylaxis.